Investigation on taxonomy, secondary metabolites and antibacterial activity of Streptomyces sediminicola sp. nov., a novel marine sediment-derived Actinobacteria - Kun Zhang; Wenping Ding; Chenghui Han; Lijuan Long; Hao Yin; Jianping Yin (Microbial Cell Factories)
Abstract Background Marine actinomycetes, especially Streptomyces, are recognized as excellent producers of diverse and bioactive secondary metabolites on account of the multiplicity of marine habitations and unique ecological conditions, which are yet to be explored in terms of taxonomy, ecology, and functional activity. Isolation, culture and genome analysis of novel species of Streptomyces to explore their potential for discovering bioactive compounds is an important approach in natural product research. Results A marine actinobacteria, designated strain SCSIO 75703 T, was isolated, and the potential for bioactive natural product discovery was evaluated based on genome mining, compound detection, and antimicrobial activity assays. The phylogenetic, phenotypic and chemotaxonomic analyses indicate that strain SCSIO 75703 T represents a novel species in genus Streptomyces, for which the name Streptomyces sediminicola sp. nov. is proposed. Genome analysis revealed the presence of 25 secondary metabolite biosynthetic gene clusters. The screening for antibacterial activity reveals the potential to produce bioactive metabolites, highlighting its value for in-depth exploration of chemical constituents. Seven compounds (1–7) were separated from the fractions guided by antibacterial activities, including three indole alkaloids (1–3), three polyketide derivatives (4–6), and 4-(dimethylamino)benzoic acid (7). These primarily antibacterial components were identified as anthracimycin (4), 2-epi-anthracimycin (5) and β-rubromycin (6), presenting strong antibacterial activities against Gram-positive bacteria with the MIC value ranged from 0.125 to 16 μg/mL. Additionally,, monaprenylindole A (1) and 3-cyanomethyl-6-prenylindole (2) displayed moderate inhibitory activities against α-glucosidase with the IC50 values of 83.27 and 86.21 μg/mL, respectively. Conclusion Strain SCSIO 75703 T was isolated from marine sediment and identified as a novel species within the genus Streptomyces. Based on genomic analysis, compounds isolation and bioactivity studies, seven compounds were identified, with anthracimycin and β-rubromycin showing significant biological activity and promising potential for further applications.